Aluminum Incorporation Impacts on Some Physical Properties of Pure CdO Film Synthesized by Spray Pyrolysis - Ninet M. Ahmed (Universiti Malaysia Perlis (UniMAP), 2018)
Link to publisher's homepage at http://ijneam.unimap.edu.my/